Navigation sensors and systems in GNSS degraded and denied environments - Schmidt, George T. (Chinese journal of aeronautics, 2015)
Position, velocity, and timing（PVT） signals from the Global Positioning System（GPS）are used throughout the world but the availability and reliability of these signals in all environments has become a subject of concern for both civilian and military applications. This presentation summarizes recent advances in navigation sensor technology, including GPS, inertial, and other navigation aids that address these concerns. Also addressed are developments in sensor integration technology with several examples described, including the Bluefin-21 system mechanization.